DIABETIC GANGRENE OF THE LOWER EXTREMITIES – ANALYSIS OF TREATMENT RESULTS AND LONG-TERM SURVIVAL OUTCOMES - A. R. Bababekov; U. K. Kasimov (Modern American Journals, 2025)
Diabetic ulcers are not only a common problem but also one of the serious and costly complications of diabetes. Significant risk factors for amputation in patients include: male gender, history of nicotine use, duration of foot ulcers, presence of destructive changes in the foot, and excess body weight. A history of ulcers increases the risk of developing another ulcer in patients with diabetes. Between 20% and 58% of patients develop a new ulcer within a year after wound healing. Studies have shown that patients with recurrent diabetic foot ulcers have a 2.23 times higher rate of amputation compared to patients with primary foot ulcers [7,8,12]. Objective. To study long-term survival and treatment outcomes in patients with diabetic gangrene and necrotic complications (DGNC) after limb amputation at various levels.
Keywords: Neuroischemic form of diabetic foot syndrome, diabetic ulcer, diabetes mellitus, critical ischemia of the lower extremities.